(untitled) (Pedagogy of Higher and Secondary Education, 2022)
About the problem of "information culture" and "informmotion competence". Kryvyi Rig state pedagogical university. Abou the problem of "information cuture" and "information comperence of a personality in the condition of swift normalization of society.